Bridging mathematics and communication: Implementing realistic mathematics education principles for skill development - Siswantari; Sabon, Simon Sili; Listiawati, Nur; Wirda, Yendri; Zulkardi; Riyanto, Bambang (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Effective mathematical communication is essential for developing conceptual understanding and applying mathematics in real-life contexts. However, empirical studies consistently report that students' mathematical communication skills remain insufficiently developed, highlighting a critical gap in instructional practices that effectively foster these competencies. The Realistic Mathematics Education (RME) approach, grounded in six core principles—reality, levels, intertwinement, activity, interactivity, and guidance—has demonstrated promise in promoting meaningful and contextualized learning. Yet, there is limited empirical research that systematically investigates how these principles specifically support the enhancement of students’ mathematical communication. This study addresses that gap by examining how the application of RME principles contributes to the development of communication skills in junior high school mathematics classrooms. Utilizing a qualitative research design, data were gathered from nine schools across three districts through focus group discussions, lesson plan analysis, and classroom observations. Participants included RME experts, education policymakers, school principals, and mathematics teachers. Thematic analysis was conducted to identify how the six RME principles are operationalized in practice and how they align with indicators of students’ mathematical communication. The findings reveal that each principle plays a distinct yet interconnected role in supporting communication—particularly through meaningful contexts, dialogic interactions, and structured teacher guidance. The study offers empirical support for the broader adoption of RME and highlights its potential to increase teacher motivation and instructional quality. It further underscores the importance of sustained professional development—such as mentoring and lesson study—in enhancing teachers' capacity to implement RME effectively. Future research should focus on developing RME-based instructional materials and digital tools, including GeoGebra-integrated worksheets and context-rich problem sets, to amplify its impact within mathematics education in Indonesia.